Preventive Monitoring and Early Warning of Fire Risks in Timber Heritage Buildings: A Case Study of Hualin Temple in Fuzhou, China - CHEN, Jinyi; Li, Jiajun; WU, Xin; RAO, Jintong (MAJ - Malaysia Architectural Journal, 2025)
In building fires the protection of life is priority to buildings, which normally considered as guidance rather than strict codes. However, in cases of heritage buildings, which are at extremely high risk of irreplaceable loss, fire alerts may issue warnings based on low criteria as a significant threat appears to the building. In China, the oldest existing heritage buildings are mainly wood structures, which often have extremely high fire hazards with aged low moisture timbers and the unique wood frame system making it extremely difficult to quickly salvage the building when fire occurs. To realize the preventive conservation (PC) of ancient timber structures, this study focuses on predicting the probability of fire events. Firstly, the frequency data of heritage fire events in China over the past seventy years were collected to isolate the common fire triggers. Secondly, to assess the credibility of each fire risk factor, Hualin Temple, a typical Song Dynasty wood-frame architectural heritage in Fuzhou City, Fujian Province, was selected as a case. Thirdly, fire time series data were obtained using FDS software to establish a fire dynamics model with local temperature and humidity data to simulate two fire conditions: summer and winter. Subsequently, the data were analyzed in a fuzzy inference system to predict the probability of fire occurrence. The preliminary results suggest to issue a warning when the fire confidence level is about 0.24 or more and to issue an alarm when the fire confidence level is approaching 0.5.